2018
DOI: 10.13057/nusbiosci/n100407
|View full text |Cite
|
Sign up to set email alerts
|

Production of bioethanol from sago hampas via Simultaneous Saccharification and Fermentation (SSF)

Abstract: Huang CH, Adeni DSA, Johnny Q, Vincent M. 2018. Production of bioethanol from sago hampas via Simultaneous Saccharification and Fermentation (SSF). Nusantara Bioscience 10: 240-245. Sago hampas is an inexpensive, renewable and abundant agro-industrial residue that can be exploited to produce bioethanol. In this study, ethanol production was performed via simultaneous saccharification and fermentation (SSF) on fresh sago hampas at 2.5%, 5.0% and 7.5% (w/v) feedstock loadings with the aid of amylolytic enzymes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
2
9
0
1
Order By: Relevance
“…As outlined in Table 2, dried sago hampas used in this study contained 52.03% starch, 27.82% cellulose, 5.32% hemicellulose and 3% lignin. The results obtained in this work are comparable to a previous report by Hung et al (2018), where sago hampas were reported to contain 55.4% starch, 23.6% cellulose, 9.1% hemicellulose, and 4.0% lignin. Furthermore, the starch content recorded in this study, which was in the range of 30% -50% was comparable with that reported by Awg-Adeni et al (2010).…”
Section: Simultaneous Saccharification and Fermentation (Ssf) Of Starsupporting
confidence: 90%
See 3 more Smart Citations
“…As outlined in Table 2, dried sago hampas used in this study contained 52.03% starch, 27.82% cellulose, 5.32% hemicellulose and 3% lignin. The results obtained in this work are comparable to a previous report by Hung et al (2018), where sago hampas were reported to contain 55.4% starch, 23.6% cellulose, 9.1% hemicellulose, and 4.0% lignin. Furthermore, the starch content recorded in this study, which was in the range of 30% -50% was comparable with that reported by Awg-Adeni et al (2010).…”
Section: Simultaneous Saccharification and Fermentation (Ssf) Of Starsupporting
confidence: 90%
“…Based on Figure 6, a steep decrease of total sugar content during the first 6 h indicated that the substrates present in the fermentation broth were rapidly fermented into ethanol by C. glabrata. The same observations were also reported by Hung et al (2018) who stated that not all sugars can be converted to ethanol. In addition, the results obtained in this study showed the presence of other unknown hexose sugars in the fermentation broth besides glucose.…”
Section: Simultaneous Saccharification and Fermentation (Ssf) Of Starsupporting
confidence: 83%
See 2 more Smart Citations
“…The limited petroleum reserves and serious environmental pollutions have triggered the necessity to exploit alternative renewable energy sources, such as bioethanol and biodiesel (Huang et al, 2018). Biodiesel is an outstanding renewable fuel that can supplement petroleum fuel .…”
Section: Introductionmentioning
confidence: 99%